2006
DOI: 10.1007/s10681-006-9232-2
|View full text |Cite
|
Sign up to set email alerts
|

The genus Dasypyrum––part 1. The taxonomy and relationships within Dasypyrum and with Triticeae species

Abstract: The article is an attempt to summarize available information about the relationships within Dasypyrum (Triticeae, Poaceae) and between Dasypyrum and other genera in the Triticeae. A relationship between the annual diploid D. villosum (L.) P. Candargy and the perennial tetraploid D. breviaristatum (L.) Frederiksen is discussed on the basis of cytological and molecular investigations. Although the relationship between the two Dasypyrum species seems to be quite close, D. breviaristatum is an autotetraploid with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 65 publications
0
13
0
1
Order By: Relevance
“…The genus Dasypyrum (or Haynaldia ) consists of two species, Dasypyrum villosum and D. breviaristatum. Cytological and molecular evidence suggest significant genomic diversification between the two species, and therefore the genome symbols of D. villosum and D. breviaristatum were assigned to V and V b , respectively [ 1 , 2 ]. Recently, Baum et al [ 3 ] suggested the genome constitution of tetraploid D. breviaristatum as VVV b V b (2 n = 4 x = 28) based on the evolutionary analysis of the nr5S DNA multi-gene family.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Dasypyrum (or Haynaldia ) consists of two species, Dasypyrum villosum and D. breviaristatum. Cytological and molecular evidence suggest significant genomic diversification between the two species, and therefore the genome symbols of D. villosum and D. breviaristatum were assigned to V and V b , respectively [ 1 , 2 ]. Recently, Baum et al [ 3 ] suggested the genome constitution of tetraploid D. breviaristatum as VVV b V b (2 n = 4 x = 28) based on the evolutionary analysis of the nr5S DNA multi-gene family.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Dasypyrum (or Haynaldia ) consists of 2 species: Dasypyrum villosum and D. breviaristatum. Both species are native to the Mediterranean environment and are distributed in the mountainous regions of Europe and Africa [Gradzielewska, 2006a;De Pace et al, 2011]. Cytological and molecular evidences suggest significant genomic diversification between the 2 species, and therefore, the genomes of D. villosum and D. breviaristatum were assigned the genomic symbols V and V b , respectively [Gradzielewska, 2006a;Liu et al, 2010].…”
mentioning
confidence: 99%
“…Both species are native to the Mediterranean environment and are distributed in the mountainous regions of Europe and Africa [Gradzielewska, 2006a;De Pace et al, 2011]. Cytological and molecular evidences suggest significant genomic diversification between the 2 species, and therefore, the genomes of D. villosum and D. breviaristatum were assigned the genomic symbols V and V b , respectively [Gradzielewska, 2006a;Liu et al, 2010]. Within both species of Dasypyrum , several agronomically important traits, including those of disease resistance, high protein quality, and drought tolerance, have been identified and offer valuable resources for wheat improvement [Gradzielewska, 2006b;De Pace et al, 2011].…”
mentioning
confidence: 99%
“…D. breviaristatum consists of diploid (2n = 2x = 14, V b V b ) and tetraploid (2n = 4x = 14, V b V b V b V b ) cytotypes. They are perennial allogamous species restricted to two mountainous regions in northwest Africa and in Greece and Morocco (Gradzielewska, 2006a). Species of the genus Dasypyrum contain many agronomically useful genes, which could be of value in wheat breeding for multi-disease resistance, better quality and high yield (Gradzielewska, 2006b).…”
Section: Introductionmentioning
confidence: 99%